Model Perencanaan Kawasan Pertanian di Kabupaten Karangasem, Provinsi Bali Pasca Erupsi Gunung Agung - Widhianthini Widhianthini; A.A.A. Wulandira Sawitri Djelantik (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2019)
Karangasem is one of the regencies in Bali Province that has potential in the agricultural sector, in addition to Tabanan Regency. Contribution of the agricultural sector of Karangasem Regency amounted to 14.74% of the GDP of Bali Province. Large potential of the agricultural sector can also be seen from the livelihoods of the population, where majority (50.61%) work as farmers (Statistics of Bali Province, 2017). In November 2017, Mount Agung erupted, impacted the development of sectors in Karangasem Regency, including the agricultural sector. This research is intended to determine the competitiveness of the agricultural sector (especially the food crop subsector) and the planning model of agricultural areas in the regency. Location selection is done purposively with the consideration that it has the lowest economic growth rate after Jembrana Regency and has experienced Mount Agung eruption in 2017. Research method used are Shift Share Analysis and Dynamic Modeling. Especially for Dynamic Modeling, an analysis of economic aspects was carried out. Results shows that agricultural sector in Karangasem Regency can still compete with other regions in Bali Province. The agricultural sector, especially paddy fields in the last five years (in 2012-2017), was still able to contribute to the increase of the regency's Gross Regional Domestic Product (GRDP) and community income if the agricultural area management model is implemented in an integrated manner between farmers, Village Credit Institutions, and local customary villages.